Uma revisÃ£o dos algoritmos de radicalizaÃ§Ã£o em língua portuguesa - Angel Freddy Godoy Viera; Johnny Virgil (Information Research: An International Electronic Journal)
Introduction. The significance of information retrieval has been increased as a result of the increasing frequency with which digital files are created and used. One of the many strategies for processing texts for the indexing of their contents in information retrieval systems is called stemming, which consists in the reduction of similar words to the same unvarying representation. Stemming relies on the morphological structure of the language with which it is intended to work. Aim.This paper aims at defining the concept of stemming, presenting the algorithms available for Portuguese and commenting on several topics related to the use of this type of algorithms. Method. Literature review on stemming for Portuguese known to the authors. Results. To this day, there are only three algorithms published which deal with stemming in Portuguese: Porter's, Orengo's and Gonzalez's. Conclusion. Today,improvement in terms of stemming for the Portuguese language cannot be achieved successfully, since there is little research being done in this area.